Transformasi Dakwah dalam Masyarakat Pluralistik di Indonesia - Machendrawaty, Nanih (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2002)
Seen from the pointview of ilmu dakwah, dakwah is actually a form of social change. As such, it promotes a Â distinctive form of social change easily differentiable from other social changes. This account calls this typical form of social change as dakwah transformation.This paper tries to solicite some theoretical questions concerning the dakwah transformation. Those include the direction and orientation of the transformation itself; the perspective of social change that fits the vision and meet the missions of dakwah; the supposed designers of dakwah who have the necessary competence to formulize the nature of the transformation; the concepts of the transformation that both support and underpin the vision, objectives, strategies, and programs relevant to overall plarullng of social, change within a pluralistic society. It is suggested here that the dakwah transformation be based on a management process whose main Â orientation and chief goal is achievement. Without this, the process would be both stagnant and reproductive, and in turn, the dakwah transformation would remain a dream lacking community supports.